Comparison of Buddhist and Jain Religions Among Belief and Ethical Similarities - Dadman, Enayatullah; Sultan Mohammad Stanikzai; Matiullah Taib (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The aim of this article is to Learn about the comparison between Jainism and Buddhism regarding belief and, ethical similarities, Both had the foundation of the Aryan culture and were propelled by the plain standards and the logic of the Upanishads, especially that of Sankhya-Yoga. Disregarding of God or a skeptical state of mind, negativity, or conviction that human life is full of wretchedness, the teachings of transmigration of the soul and Karma (activity or deed), and a kind of dualism between soul and matter are common to Hindu-Sankhya reasoning, Jainism and Buddhism. In this way, the source of the rationalities of both was the same in spite of the fact that both of them made certain changes in it, the research method is documentary. The information is collected in the form of documents. Finally, the research findings show that both were the products of intellectual, spiritual, and social forces of their age and therefore, both stood up as revolts against the prevalent Brahmanic religion.